Review on Cloud Computing and its Services - Nimish Das; Shantanu Sinnarkar; Chaitanya Joshi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Cloud computing is a technology that provides access to resources such as network, storage, and servers with the help of the internet on pay as you use or based on the demand. This innovative technology has the potential to revolutionize the IT sector, impacting the improvement and the choice of IT hardware, as well as raising the want of Software as a Service (Saas). It can also benefit new internet service providers by reducing the amount of investment needed for hardware and operating costs. Cloud computing also eliminates the need for worrying about over- or underprovisioning, which can lead to the inefficient use of resources and loss of consumers and income. This article provides an overview of cloud computing and highlights critical areas for future research in this rapidly developing field of computer science.